Does isolation of the left atrial posterior wall using cryoballoon ablation improve clinical outcomes in patients with persistent atrial fibrillation? A prospective randomized controlled trial. Issue 7 (9th February 2022) - Ahn, Jinhee; Shin, Dong Geum; Han, Sang Jin; Lim, Hong Euy
Abstract: Aims: Posterior wall isolation (PWI) of the left atrium (LA) adjunct to pulmonary vein isolation (PVI) by radiofrequency catheter ablation has shown favourable outcomes in patients with persistent atrial fibrillation (PeAF). This study was sought to investigate the efficacy and safety of additional PWI by cryoballoon ablation (CBA) alone in patients with PeAF. Methods and results: Patients who underwent de novo CBA for PeAF ( n = 100) were randomly assigned (1 : 1) to the PVI only group and PVI combined with PWI (PVI+PWI) group. Procedural and clinical outcomes were prospectively compared over a 12-month follow-up.  : Baseline characteristics, including mean AF duration (56.2 ± 43.2 months) and LA size (48.2 ± 7.7 mm), were well-balanced between the groups. Successful PVI was achieved in all patients. In the PVI+PWI group, complete PWI by CBA was achieved in 31 (62%) patients. The LA indwelling and procedure times were significantly longer in the PVI+PWI group. The complication rates were not different between groups. During a mean follow-up of 457.9 ± 61.8 days, the recurrence rate of atrial tachyarrhythmia was significantly lower in the PVI+PWI group than in the PVI only group (24% vs. 46%; P = 0.035). The recurrence-free survival rate was significantly higher in the PVI+PWI group compared with the PVI only group, irrespective of complete PWI (log-rank P = 0.013). Multivariate analysis showed that adjunctive PWI [hazard ratio (HR) 0.255; P = 0.003] and LA size (HR 1.079; P = 0.014) were independent predictors of clinical recurrence. Conclusion: Compared with PVI only, adjunctive PWI achieved exclusively by CBA resulted in better clinical outcomes without increasing complications in patients with PeAF.